+0  
 
0
30
1
avatar+180 

Let $f(x)$ be the polynomial \[f(x)=3x^4+5x^2-9x-2.\] If $g(x)$ is equal to the polynomial $f(x-1)$, what is the sum of the coefficients of $g$?

michaelcai  Sep 10, 2017
Sort: 

1+0 Answers

 #1
avatar+76094 
+2

 

f(x -1)  = 3(x-1)^4 + 5(x-1)^2 - 9(x-1) - 2  =

 

3 (x^4 - 4x^3 + 6x^2 - 4x + 1) + 5(x^2 - 2x + 1) - 9 (x - 1) - 2 =

 

3x^4 - 12x^3 + 23x^2 - 31x + 15  =  g(x)

 

The sum of the coefficients of g(x)  =  3 - 12 + 23 - 31 + 15  =  -2

 

 

cool cool cool

CPhill  Sep 10, 2017

22 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details